PRINSIP KEHATI-HATIAN DALAM KONSISTENSI PENERBITAN KEBIJAKAN PPAP SEBAGAI UPAYA MENCIPTAKAN STRUKTUR PERBANKAN YANG SEHAT - Johannes Ibrahim; P. Lindawaty S. Sewu; Hassanain Haykal (JURNAL LITIGASI (e-Journal), 2013)
Banks are intermediary institutions that play a role in improving the quality of life, in which the bank to collect funds from the public in the form of savings and channel them back in the form of loans. Given the role and functions of the bank are very strategic, and management of the bank should do well. Good bank management should refer to the statutory provisions and adhere to the prudential principle. One form of management of the bank in an effort to create a healthy banking-based risk management is to make Establishment Allowance for Earning Assets (PPAP) for non-performing loans. Establishment Allowance for Earning Assets (PPAP) on its implementation should be done consistently, so the need for intensive supervision of Bank Indonesia and the importance of coherence of legislation that serves as an umbrella act for the general operations of the bank Keywords: Prudential Principle, PPAP and Banking Structure.